Teachers' Perceptions toward the Implementation of 2013 Curriculum - Farida Keni Nurhayati; Sri Samiati Tarjana; Hersulastuti Hersulastuti (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Teachers' perceptions toward the implementation of new curriculum is one of fascinating topic to be discussed. This study discovers teachers' perceptions toward the implementation of 2013 curriculum, investigates factors affecting the application of 2013 curriculum, and identifies the effect of their perceptions into classroom practice. Through qualitative design, the study was conducted at one of private junior high schools in Solo, Central Java. The data were collected by interviewing, administering questionnaire, observing the classroom practices and reviewing the documents. The findings reveals that; (1) teachers have positive perceptions toward 2013 curriculum (2) there are four factors which influence teachers' perceptions toward the implementation of 2013 curriculum, which include teaching experience; educational background, teaching training, teachers' personal experience; (3) teachers' perceptions contribute significantly in influencing teacher's decision making in the classroom related to the choice of learning and activities for students. Since teachers' perceptions have a powerful impact on teachers' classroom practices, teachers are required to improve their competences and keep up with the advance of knowledge and technology.